Determinan Pengungkapan Kebijakan Anti Korupsi Ditinjau dari Good Corporate Governance dan Reputasi Auditor - Stefani Lily Indarto (Journal of Trends Economics and Accounting Research, 2023)
Corruption is a major challenge as well as a problem in an organization or business. Economic development will weaken and corporate accountability will be lost due to corruption. As a result of corruption, it will have a negative impact in various fields, including on the country's economy. For this reason, company awareness is needed in disclosing anti-corruption policies as a form of minimizing the occurrence of corruption in the business world. Even the Indonesian Financial Services Authority (OJK) also explains the recommendations for disclosing anti-corruption policies to every company that goes public in its annual report. The internal control mechanism can be a key factor in fostering information disclosure so that it will reduce the potential for loopholes for acts of fraud. Good Corporate Governance (GCG) is intended as a tool that minimizes fraud. In addition, by using a reputable public accounting firm, it is hoped that it can also show a more convincing and quality reputation and will be more motivated to disclose information, especially related to efforts to prevent corruption. The purpose of this study is to determine the effect of Good Corporate Governance (board of directors size, board of commissioners' independence, audit committee meeting frequency, and governance committee) and auditor's reputation on anti-corruption policy disclosure. This research uses all companies listed on the Indonesia Stock Exchange in the 2019-2021 period using a purposive sampling method. From 1739 companies, the results obtained were that the independence of the board of commissioners, governance committee, and auditor reputation had a positive effect on disclosing anti-corruption policies. Meanwhile, the size of the board of directors and the frequency of audit committee meetings have no effect on anti-corruption policies.